Analisis Pengaruh Besar Gesekan Terhadap Tegangan Thermal Pada Sepatu Rem Mobil Ketebalan 2 mm Menggunakan Perangkat Lunak Msc.Nastran V.9 - Sudirman Lubis (Fakultas Teknik UMSU, 2019)
Braking failure better known as brake failure is caused by many factors, but one factor is due to excess heat that occurs in optimal braking conditions when the vehicle is driving at high speed and sufficient distance. The purpose of this research is to obtain the result of thermal stress simulation during braking, in special area of brake shoe with 8 mm thickness. However, it is unlikely that brake shoe is analyzed manually because brake shoes have many vertices, even up to thousands of vertices. So we need the software support finite element finishing method of MSC. NASTRAN V9 to simulate the distribution of temperature distribution on brake shoe for easy analysis. Thermal voltage that occurs in brake boots with a thickness of 2 mm in this study that brake shoe design model 2 has a maximum thermal voltage of 4.5701 Mpa and 2.5295 Mpa Minimum lower than the brake shoes model 1 maximum thermal voltage of 4.5585 Mpa and 2,5225 Mpa Minimum. With a maximum test difference of 0.25% and a minimum of 0.27%.